Dual role of pyroptosis in liver diseases: mechanisms, implications, and therapeutic perspectives - Yang, Siyuan; Zou, Yunyi; Zhong, Chunhua; Zhou, Zuoqiong; Peng, Xiyang; Tang, Changfa (Frontiers in Cell and Developmental Biology, 2025)
Pyroptosis, a form of programmed cell death induced by inflammasome with a mechanism distinct from that of apoptosis, occurs via one of the three pathway types: classical, non-classical, and granzyme A/B-dependent pyroptosis pathways. Pyroptosis is implicated in various diseases, notably exhibiting a dual role in liver diseases. It facilitates the clearance of damaged hepatocytes, preventing secondary injury, and triggers immune responses to eliminate pathogens and damaged cells. Conversely, excessive pyroptosis intensifies inflammatory responses, exacerbates hepatocyte damage and promotes the activation and proliferation of hepatic stellate cells, accelerating liver fibrosis. Furthermore, by sustaining an inflammatory state, impacts the survival and proliferation of cancer cells. This review comprehensively summarizes the dual role of pyroptosis in liver diseases and its therapeutic strategies, offering new theoretical foundations and practical guidance for preventing and treating of liver diseases.